Financial Determinants of Manufacturing Inventory Behavior–A Quarterly Study Based on United States Estimates: 1947-61 - Kuznets, Paul W. (Journal of Finance, 1965)
Paul W. Kuznets, Financial Determinants of Manufacturing Inventory Behavior–A Quarterly Study Based on United States Estimates: 1947-61, The Journal of Finance, Vol. 20, No. 1 (Mar., 1965), pp. 107-108